The Intention of Community Garden Participation: A Case Study in Community Garden of Taman Tasik Ilmu, Kota Seriemas - Nurzawani, Azuwa (INTI International University, 2024)
Malaysia's population is projected to reach approximately 41.5 million by 2040, marking a significant increase from its current population. This projection is based on various factors, including birth rates, death rates, and migration trends. With this rapid population increase, the urbanization rate is expected to rise, leading to concerns about food security. Ensuring food security becomes a pressing issue, as the country must produce or import enough food to feed its population. This is where community garden programs and other local food production initiatives can play a significant role in supplementing food supply and promoting sustainable agriculture. The United Nations' Sustainable Development Goals (SDGs) introduced in 2015, specifically Goal No. 2 (Zero Hunger), emphasize the need to address food security issues. One of Malaysia's strategies to achieve Goal No. 2 is through the implementation of community garden programs. However, the success of such programs largely depends on the intention and volunteerism of community participants. This study aims to explore the intention behind community garden participation at Taman Tasik Ilmu. Data was collected using an online questionnaire with 40 participants. The questionnaire gathered information on demographics, gardening knowledge, reasons for participation, and opinions on facilities and garden management. Descriptive analysis was employed to analyze the collected data. The results indicated that the primary motivation for participants to join the community garden program was to fill their free time. This finding suggests that aligning the objectives of community garden programs with the intentions of participants may enhance their success and sustainability.